Pengaruh Brain Gym Terhadap Perubahan Nilai Fungsi Kognitif Pada Lansia Demensia Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Padang Pariaman 2025 - Suci Rahayu; Eri Wahyudi; Helmanis Suci (CV. ITTC INDONESIA, 2026)
The prevalence of dementia is estimated at 55 million people suffering from dementia in the world. Indonesia is estimated to have 1.2 million people. Dementia is common in the elderly. Elderly people with dementia have an impact on becoming more withdrawn and unable to control their behavior. Their moods often change and they like to walk around (wander). In the elderly, decreased brain and body abilities make the body susceptible to illness, dementia and frustration. The purpose of this study was to determine the effect of brain gym on changes in cognitive function scores in elderly with dementia at the Sabai Nan Aluih Sicincin Padang Pariaman Social Home. The method in this study was quantitative with a pre-experimental design, one group pretest-posttest approach. The study was conducted at the Sabai Nan Aluih Sicincin Padang Pariaman Social Home. The population of all elderly people with cognitive disorders at the Sabai Nan Aluih Sicincin Padang Pariaman Social Home was 40 people with a sample of 15 people. The sampling technique was purposive sampling. Data were collected using a questionnaire. Univariate and bivariate data analysis used the Paired Sample T-Test. The results of the study showed that the average cognitive function score before brain gym was 14.40. The average cognitive function score after brain gym was 25.47. There is an effect of brain gym on changes in cognitive function values ​​in elderly with dementia at the Tresna Werda Sabai Nan Aluih Sicincin Padang Pariaman Social Home in 2025 (p value = 0.000). The conclusion of this study is that there is an effect of Brain Gym on changes in cognitive function values ​​in elderly with dementia. It is hoped that through the leadership of the Tresna Werdha social home, Brain Gym can be made a routine activity for the elderly.